Prevalence of SARS-CoV-2 antibodies among Swiss hospital workers: Results of a prospective cohort study - Kohler, Philipp P. (Infect Control Hosp Epidemiol, 2020)
In this prospective cohort of 1,012 Swiss hospital employees, 3 different assays were used to screen serum for SARS-CoV-2 antibodies. Seropositivity was 1%; the positive predictive values of the lateral-flow immunoassay were 64% (IgG) and 13% (IgM). History of fever and myalgia most effectively differentiated seropositive and seronegative participants.